1981
DOI: 10.1136/hrt.45.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Variability of electrocardiographic and enzyme evolution of myocardial infarction in man.

Abstract: We have studied the time course of development of ST segment elevation, R wave loss, and Q wave development in 41 patients using 35 lead praecordial mapping or 12 lead electrocardiograms in those with anterior and inferior infarcts, respectively. The first recording was at a mean time of six hours after the onset of pain; subsequent records were taken every eight hours for 24 hours, every 12 hours for the second day, and every day thereafter. Serial CK MB estimates were obtained at every four hours for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Enzyme release was smaller in the metoproloi group unrelated to the site and type of infarction. The benefit of late-entry patients may be due to more subtotal occlu sions in late-entry patients [17] and due to continuation of cell death for 24 h or longer based on serial ECG R wave measurements and CK-MB release [18], Yet, our result on enzyme release is not consistent with the whole MIAMI material. In the latter a smaller enzyme release was found only in patients randomized early, but not in those randomized later than 7 h after the onset of symptoms [19].…”
Section: Infarct Sizecontrasting
confidence: 56%
“…Enzyme release was smaller in the metoproloi group unrelated to the site and type of infarction. The benefit of late-entry patients may be due to more subtotal occlu sions in late-entry patients [17] and due to continuation of cell death for 24 h or longer based on serial ECG R wave measurements and CK-MB release [18], Yet, our result on enzyme release is not consistent with the whole MIAMI material. In the latter a smaller enzyme release was found only in patients randomized early, but not in those randomized later than 7 h after the onset of symptoms [19].…”
Section: Infarct Sizecontrasting
confidence: 56%
“…Most of the damage occurs during the first 6-12 h. About 50% of ECG signs of necrosis is com plete within 6 h, 75% within 12 h and nearly all by 18-24 h after the onset of pain [14], The frequency of pain and arrhythmias are highest during the first few hours; their fre quency then decreases rapidly [15]. Conse- Fig.…”
Section: The Importance Of Starting Treatment Intravenously and Earlymentioning
confidence: 99%
“…Praecordial mapping showed that after six hours only about half of the total R wave loss had occurred, and we speculated whether up to this time the size of the infarct could be modified by treatment, (Figure 1 in Yusuf et al, 1981). The natural history of untreated infarction was not consistent: some (type A) produced a rapid CKMB release, but in an equal number (type B), the total release was slower and peaked at times up to 32 hours.…”
Section: Introduction 10cmentioning
confidence: 99%